A study on existing gaps in current antenatal care and new WHO model of routine antenatal care: need for implementation of new WHO guidelines on antenatal care - Kulkarni, Tanaya G.; Patil, Sujata V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Antenatal care is essential for ensuring good maternal and neonatal health outcomes, yet significant gaps remain in its delivery. In 2016, the WHO introduced new antenatal care guidelines increasing the number of antenatal contacts to 8, from the old 4 visit approach. The new model focuses on strengthening the connection between health care workers and pregnant women receiving antenatal care. However, utilization rate for the level of recommended antenatal care is still low especially in developing countries like India, thus further highlighting the need for identifying and bridging the gaps in antenatal care delivery. This study critically assessed the current challenges with antenatal care delivery by healthcare workers, aiming to identify gaps in existing practices and evaluate the need for implementing the New WHO antenatal care guidelines (2016). Methods: A qualitative type of cross-sectional study was conducted at a tertiary care hospital in western Maharashtra, India among 128 mothers who were admitted to the post-natal ward of the hospital. Data collection was done using a pretested, prevalidated questionnaire, descriptive statistics were used to summarise the data. Results: The study found that while 92% of women had recommended number of antenatal care contacts in the first and second trimester, while none had five antenatal care contacts in the third trimester. 50% of mothers had below recommended IFA consumption. Regarding nutritional counselling and non-pharmacological management of common pregnancy symptoms only 5.46% received guidance on nausea and 29.68% on heartburn management. All participants received respectful maternal care aligning with the WHO guidelines. Conclusions: The findings demonstrate the need for active implementation of the new 2016 WHO’s guidelines on antenatal care to enhance the quantity and quality of antenatal care delivered. Ensuring that healthcare workers provide recommended education, immunization, supplementation, and maternal support throughout pregnancy. Identifying and bridging these gaps will help improve maternal and neonatal health outcomes, aligning practices with global standards and contributing to positive pregnancy experiences for pregnant women.